Development of korfball games based on teaching games for understanding for elementary school - Riyanto, Adnan; Widiyanto, Widiyanto (Journal of Education, Health and Sport, 2021)
The purpose of this study is to produce a modification of the basketball-based game. This research is a research and development (Research and Development). The stages of research on the development of the Borg & Gall model that have been adopted into seven stages, namely: needs analysis, planning, developing initial products in the form of making initial products which are validated by material experts, media experts, and practitioners. Furthermore, the product is tested on students through small group trials, revisions, field trials and final product revisions. The subjects of this study were the upper grade students of SD Negeri Bakalan, SD Negeri Ledoknongko and SD Negeri Jongkang totaling 30 students in total, with 10 students in each elementary school. The data collection instrument used a questionnaire and an evaluation sheet. The quantitative data analysis technique in this study used descriptive statistical analysis. The results of the study were in the form of TGfU-based basketball game material in the form of a book consisting of six games as a learning tool. The material expert’s assessment is included in the criteria of "very good" with an average of 4.9, then media experts indicate the criteria of "very good" with an average of 4.7, and practitioners include the criteria of "very good" with an average of 4.9, while the material field trials The TGfU-based basketball game that was tested on students showed the criteria of "very good" with an average score of 4.37. It can be concluded that the development of TGfU-based basketball game material is feasible to be used as a means of learning big ball games in physical education lessons in elementary schools.